2017
DOI: 10.3844/crdsp.2017.8.14
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of Orthodontic Resins: <i>In vitro</i> Evaluation of Monomer Leaching and Cytotoxic Effects

Abstract: Abstract:The aim of this study was to investigate the effect of orthodontic resins on cell survival and to evaluate monomer leaching both before and after resin polymerization. Materials and methods: 3T3 mouse fibroblasts were exposed to three cured and uncured orthodontic resins. Cellular viability was assessed by Alamar Blue assay after 24, 48 and 72 h. High Performance Liquid Chromatography was used to measure the amount of monomers released by the tested samples. Data were analyzed by means of ANOVA and Tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Uomo et al (2017) determined effect of orthodontic resins (Eagle Spectrum, Grengloo and Transbond XT) on cell viability by Alamar Blue test and evaluated released monomer both before and after resin polymerization using HPLC. The results showed the role of polymerized resin in determining cytotoxic effect of orthodontic resins and suggested that differences in chemical composition of resin matrix appeared to be much more related to decrease in cell viability than amount of monomer released from orthodontic resins.…”
Section: Discussionmentioning
confidence: 99%
“…Uomo et al (2017) determined effect of orthodontic resins (Eagle Spectrum, Grengloo and Transbond XT) on cell viability by Alamar Blue test and evaluated released monomer both before and after resin polymerization using HPLC. The results showed the role of polymerized resin in determining cytotoxic effect of orthodontic resins and suggested that differences in chemical composition of resin matrix appeared to be much more related to decrease in cell viability than amount of monomer released from orthodontic resins.…”
Section: Discussionmentioning
confidence: 99%